Ethnic characterization of a population of children exposed to high doses of arsenic via drinking water and a possible correlation with metabolic processes - Bobillo, Maria Cecilia (2014)
Because the ratio between the two major arsenic metabolites is related to the adverse health effects of arsenic, numerous studies have been performed to establish a relationship between the ability to metabolically detoxify arsenic and other variables, including exposure level, gender, age and ethnicity. Because ethnicity may play a key role and provide relevant information for heterogeneous populations, we characterized a group of 70 children from rural schools in the Argentinean provinces of Chaco and Santiago del Estero who were exposed to high levels of arsenic. We used genetic markers for maternal, paternal and bi-parental ancestry to achieve this goal. Our results demonstrate that the Amerindian maternal linages are present in 100% of the samples, whereas the Amerindian component transmitted through the paternal line is less than 10%. Informative markers for autosomal ancestry show a predominantly European ancestry, in which 37% of the samples contained between 90 and 99% European ancestry. The native American component ranged from 50 to 80% in 15.7% of the samples, and in all but four samples, the African component was less than 10%. Correlation analysis demonstrated that the ethnicity and the ratio of the excreted arsenic metabolites monomethyl arsenic and dimethyl arsenic are not associated, dismissing a relationship between ethnic origin and differential metabolism.